Minimizing the stressed state of a plate with a hole and cracks. Issue 2 (1st February 2020) - Mirsalimov, Vagif M.
ABSTRACT: A theoretical analysis to determine the optimal shape of the hole for an isotropic elastic plate weakened by an arbitrary system of cracks is performed based on the minimax criterion. A criterion and a method for solving the problem of prevention of the fracture of a plate with a hole under the action of the given system of external loads are proposed. A closed system of algebraic equations is obtained, allowing minimization of the stress state and stress intensity factors depending on geometric and mechanical characteristics of the plate. The optimal shape of the hole thus determined provides an increase in the load-bearing capacity of the plate.